Relationship between onset of psoriasis and spondyloarthritis symptoms with clinical phenotype and diagnosis: data from REGISPONSER registry. (August 2022) - Gómez-Garcia, Ignacio; García-Puga, Teresa; Font-Ugalde, Pilar; Puche-Larrubia, Maria Angeles; Barbarroja, Nuria; Ruiz-Limón, Patricia; Escudero-Contreras, Alejandro; Collantes-Estévez, Eduardo; López-Medina, Clementina
Background: The relationship of psoriasis and spondyloarthritis (SpA) is well-known, and the age of appearance of different manifestations has been described as a determinant of SpA phenotype. However, differences between Spa with psoriasis and psoriatic arthritis (PsA) are still controversial. Objectives: To evaluate whether the time of onset of psoriasis relative to the appearance of rheumatic symptoms in patients with SpA is associated with a clinical phenotype, a rheumatologist's diagnosis and the evolution of the disease. Design: This was a cross-sectional study with data extracted from the REGISPONSER (Spondyloarthritis Registry of the Spanish Rheumatology Society) registry. Methods: All patients had data available for both psoriasis and SpA dates of onset. Patients were classified into two groups depending on the time of appearance of psoriasis: psoriasis before or after rheumatic symptoms. The clinical characteristics, disease activity, radiographic damage, functional ability and received treatments were compared between the two groups. Moreover, the rheumatologists' diagnoses were compared between the two groups. Univariate and multivariate logistic regressions were conducted to evaluate the factors associated with each group. Results: A total of 433/2367 (18.3%) patients included in the REGISPONSER database had psoriasis: 330 (76.2%) patients had psoriasis before rheumatic symptoms, and 103 (23.8%) had psoriasis after rheumatic symptoms. Patients with psoriasis before rheumatic symptoms had a shorter disease duration and a lower body mass index, a lower prevalence of both HLA-B27 antigens and anterior uveitis, a higher prevalence of dactylitis and an increase in levels of the erythrocyte sedimentation rate (ESR). Furthermore, a higher prevalence of PsA diagnoses (78.1% versus 56.4%) and a more frequent fulfilment of the CASPAR criteria (57.5% versus 42.2%) were found in these patients. The use of DMARDs was not significantly different between the two groups. Conclusion: The time of appearance of psoriasis is associated with the clinical phenotype of SpA and could determine a diagnosis of PsA by rheumatologists.